Portal Univerze v Mariboru - Ojsteršek, Milan (Uporabna informatika (Ljubljana), 2004)
University of Maribor has established a portal, which enables its students and employees to access to its information system, contents and distance learning support. Basic features of the portal are document management, search facility, integration of contents and services, information categorization, independency of data from different user interfaces and electronic media, multilingual support, authorization of access to data and services, contents and user interface personalization. The portal serves as a tool for communication among employees and students. The portal also includes a distance learning support service, which is integrated with the University of Maribor information system. The distance learning service consists of lecturer support, student support, administration support, digital library, and electronic dictionary parts.
Keywords: informacijski sistemi; portali; Univerza v Mariboru